B29 When real time ultrasound guided caudal block is the only feasible option: a case report. (11th August 2022) - Oweidat, A; Karroum, R; Farid, I; Harb, A; Bhalla, T
Abstract : Background and Aims: Kagami ogata syndrome (KOS)patients present with craniofacial dysmorphism, thoraco abdominal abnormalities, and kyphoscoliosis.The choice of regional anesthesia poses a real challenge as the reliance on the usual regional anesthetic techniques including lumbar epidural, paravertebral, fascial plane blocks, and landmark caudal blocks can be very challenging. Methods: We elected to perform a real time ultrasound (US) guided caudal epidural block (CEB) in a patient with a medically challenging spine anatomyto identify the midline, depth, and level with spread of local anesthesia into the caudal epidural space. Results: Conclusions: This report should encourage pediatric anesthesiologists to familiarize themselves with ultrasound guided caudal blocks as certain situations will dictate such a need.